Characterization and evaluation of Majia pomelo seed oil: A novel industrial by-product - Shao-min Pu; Rui-hong Liang; Juan Chen; Cheng-mei Liu; Chang-jin Xu; Ming-shun Chen; Jun Chen (Food Chemistry Advances, 2022)
In this study, the oil yield, chemical composition, physicochemical properties, cytotoxicity, and cell antioxidant capacity of Majia pomelo seed oils obtained by hot pressing (HP), solvent extraction (SE), and aqueous enzymatic extraction (AEE) were investigated and compared. The results showed that the seeds had 39.32% lipid, mainly composed of unsaturated fatty acids (65.01%-65.60%), notably linoleic acid (40.16%-40.79%) and oleic acid (19.22%-20.24%). The beneficial minor components and antioxidant activity of the oils were significantly influenced by processing methods. HP oil exhibited higher phytosterols (2350.55 mg/kg), tocopherol (124.85 mg/kg), and total phenolic (496.97 mg GAE/kg) contents, as well as stronger cell antioxidant activity (483.50 µmol of QE per 100 g oil), but relatively lower melting temperature (7.72°C), compared with SE and AEE oils. In addition, the oil was not toxic to normal liver LO2 cells. Overall, Majia pomelo seed oil might be a potentially valuable source for applications in the food, pharmaceutical and cosmetic industries.